2016
DOI: 10.3390/molecules21121645
|View full text |Cite
|
Sign up to set email alerts
|

Excited-State Dynamics of Melamine and Its Lysine Derivative Investigated by Femtosecond Transient Absorption Spectroscopy

Abstract: Melamine may have been an important prebiotic information carrier, but its excited-state dynamics, which determine its stability under UV radiation, have never been characterized. The ability of melamine to withstand the strong UV radiation present on the surface of the early Earth is likely to have affected its abundance in the primordial soup. Here, we studied the excited-state dynamics of melamine (a proto-nucleobase) and its lysine derivative (a proto-nucleoside) using the transient absorption technique wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 37 publications
1
19
0
Order By: Relevance
“…The photoluminescence decay lifetime of g‐CN measured herein is close to the reported photoluminescence lifetime of g‐CN prepared at a calcination temperature of 550 °C . In addition, the fluorescence lifetime of melamine is quite short and close to the IRF timescale, which indicates that there is almost no fluorescence emission from melamine; this agrees with the reported result for a study of its excited dynamics . Kohler et al.…”
Section: Resultsmentioning
confidence: 96%
See 2 more Smart Citations
“…The photoluminescence decay lifetime of g‐CN measured herein is close to the reported photoluminescence lifetime of g‐CN prepared at a calcination temperature of 550 °C . In addition, the fluorescence lifetime of melamine is quite short and close to the IRF timescale, which indicates that there is almost no fluorescence emission from melamine; this agrees with the reported result for a study of its excited dynamics . Kohler et al.…”
Section: Resultsmentioning
confidence: 96%
“…[26] In addition, the fluorescencel ifetime of melaminei sq uite short and close to the IRF timescale, whichi ndicatest hat there is almost no fluorescencee mission from melamine; this agrees with the reported result for as tudy of its excited dynamics. [27] Kohler et al explored the excited-state dynamics of melamine in aqueous solution and observed that the excited melamine molecules could decay to the electronic ground state within tens of picoseconds after excitation at l = 240 nm. [27] UV/Vis Absorption Spectra, Fluorescence Spectra, and Fluo-rescenceDecay of an AqueousSolution of Melem…”
Section: Fluorescence Decay Measurements On Melemmentioning
confidence: 99%
See 1 more Smart Citation
“…The excited-state lifetime of the lysine derivative is slightly longer (18 ps), but the dominant deactivation pathway is otherwise the same as for melamine. In both cases, the vast majority of excited molecules return to the electronic ground state on the aforementioned time scales, but a minor population is trapped in a long-lived triplet state 91 .…”
Section: Derivativesmentioning
confidence: 99%
“…Gustavsson, Markovitsi, and co-workers [ 25 ] report on the time-resolved fluorescence decay and fluorescence anisotropy measurements of seven mono-, di-, and tri-methylated xanthine derivatives in water and in methanol. Kohler and co-workers [ 26 ] study the excited-state dynamics of melamine (a proto-nucleobase) and its lysine derivatives by using time-resolved infrared spectroscopy. Mališ and Došlić [ 27 ] present a comparative computational investigation concerning the excited-state dynamics of three neutral model peptides containing the phenylalanine residue, with a focus on the role that chemical substitution and solvation play on their nonradiative relaxation pathways.…”
mentioning
confidence: 99%